Host-mediated beneficial effects of phytochemicals for prevention of avian coccidiosis - Park, Inkyung; Nam, Hyoyoun; Wickramasuriya, Samiru S.; Lee, Youngsub; Wall, Emma H.; Ravichandran, Sripathy; Lillehoj, Hyun S. (Frontiers in Immunology, 2023)
In vitro and in vivo studies were conducted to evaluate the beneficial effects of green tea extract (GT), cinnamon oil (CO), and pomegranate extract (PO) on avian coccidiosis. In experiment (EXP) 1, an in vitro culture system was used to investigate the individual effects of GT, CO, and PO on the proinflammatory cytokine response and integrity of tight junction (TJ) in chicken intestinal epithelial cells (IEC), on the differentiation of quail muscle cells and primary chicken embryonic muscle cells, and anticoccidial and antibacterial activities against Eimeria tenella sporozoites and Clostridium perfringens bacteria, respectively. In EXP 2 and 3, in vivo trials were carried out to study the dose-dependent effect of blended phytochemicals (GT, CO, PO) on coccidiosis in broiler chickens infected with E. maxima. For EXP 2, one hundred male broiler chickens (0-day-old) were allocated into the following five treatment groups: Control group for non-infected chickens (NC), Basal diet group for E. maxima-infected chickens (PC), PC group supplemented with phytochemicals at 50 (Phy 50), 100 (Phy 100), and 200 (Phy 200) mg/kg feed diets for E. maxima-infected chickens. For EXP 3, one hundred twenty male broiler chickens (0-day-old) were allocated into the following six treatment groups: NC, PC, PC supplemented with phytochemicals at 10 (Phy 10), 20 (Phy 20), 30 (Phy 30), and 100 (Phy 100) mg/kg feed for E. maxima-infected chickens. Jejunum samples were used to measure cytokine, TJ protein, and antioxidant enzyme responses at 8 days post-infection (dpi). In vitro, CO and PO reduced LPS-induced IL-1β and IL-8 in IEC, respectively, and GT enhanced the gene expression of occludin in IEC. In vivo, chickens fed a diet supplemented with phytochemicals showed enhanced BW and decreased proinflammatory cytokines following E. maxima challenge. In conclusion, the combination of GT, CO, and PO in the diet of broiler chickens infected with E. maxima induced enhanced host disease resistance including innate immunity and gut health, which contributed to improved growth and reduced disease responses. These findings provide scientific support for the development of a novel phytogenic feed additive formula that enhances the growth and intestinal health of broiler chickens infected with coccidiosis.